In vitro and in vivo genotoxic effects of straight versus tangled multi-walled carbon nanotubes. Issue 6 (2nd July 2016) - Catalán, Julia; Siivola, Kirsi M.; Nymark, Penny; Lindberg, Hanna; Suhonen, Satu; Järventaus, Hilkka; Koivisto, Antti J.; Moreno, Carlos; Vanhala, Esa; Wolff, Henrik; Kling, Kirsten I.; Jensen, Keld Alstrup; et al.
Abstract: Some multi-walled carbon nanotubes (MWCNTs) induce mesothelioma in rodents, straight MWCNTs showing a more pronounced effect than tangled MWCNTs. As primary and secondary genotoxicity may play a role in MWCNT carcinogenesis, we used a battery of assays for DNA damage and micronuclei to compare the genotoxicity of straight (MWCNT-S) and tangled MWCNTs (MWCNT-T) in vitro (primary genotoxicity) and in vivo (primary or secondary genotoxicity). C57Bl/6 mice showed a dose-dependent increase in DNA strand breaks, as measured by the comet assay, in lung cells 24 h after a single pharyngeal aspiration of MWCNT-S (1–200 μg/mouse). An increase was also observed for DNA strand breaks in lung and bronchoalveolar lavage (BAL) cells and for micronucleated alveolar type II cells in mice exposed to aerosolized MWCNT-S (8.2–10.8 mg/m 3 ) for 4 d, 4 h/d. No systemic genotoxic effects, assessed by the γ-H2AX assay in blood mononuclear leukocytes or by micronucleated polychromatic erythrocytes (MNPCEs) in bone marrow or blood, were observed for MWCNT-S by either exposure technique. MWCNT-T showed a dose-related decrease in DNA damage in BAL and lung cells of mice after a single pharyngeal aspiration (1–200 μg/mouse) and in MNPCEs after inhalation exposure (17.5 mg/m 3 ). In vitro in human bronchial epithelial BEAS-2B cells, MWCNT-S induced DNA strand breaks at low doses (5 and 10 μg/cm 2 ), while MWCNT-T increased strand breakage only at 200 μg/cm 2 . Neither of the MWCNTs was able to induce micronuclei in vitro . Our findings suggest that both primary and secondary mechanisms may be involved in the genotoxicity of straight MWCNTs.